REVIEW OF DATABASE AND PROMINENT PROGRAMMES (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Databases and database systems have become an essential component of everyday life in modern society. In the course of a day, most of us encounter several activities that involve some interaction with a database. For example, if we go to the bank to deposit or withdraw funds, if we make a hotel or airline reservation, if we access a computerized library catalog to search for a bibliographic item, or if we buy some item such as a book, toy, or computer- form on internet vendor through it Web page, there might be chances that our activities will involve someone or some computer program accessing a database, even purchasing items from a supermarket nowadays in many cases involves an automatic update of the database that keeps the inventory of supermarket items. So in this paper we will talk about how to manage the different type of data involved in any form in the database.